High-dose inhaled Salbutamol does not improve 10-km cycling time trial performance - Koch, S.; Ahn, J. R.; Koehle, M. S. (Medicine & Science in Sports & Exercise, 2015)
Background: ß2-agonists are on the World Anti-Doping Agency`s list of prohibited substances; however, athletes are allowed to treat symptoms of exercise-induced bronchoconstriction with a maximal daily dose of 1600 µg of salbutamol when taken by inhalation.